Microscopy Observations of Habitable Space in Biochar for Colonization by Fungal Hyphae From Soil - Noraini M Jaafar; Peta L Clode; Lynette K Abbott (Journal of Integrative Agriculture)
Biochar is a potential micro-environment for soil microorganisms but evidence to support this suggestion is limited. We explored imaging techniques to visualize and quantify fungal colonization of habitable spaces in a biochar made from a woody feedstock. In addition to characterization of the biochar, it was necessary to optimize preparation and observation methodologies for examining fungal colonization of the biochar. Biochar surfaces and pores were investigated using several microscopy techniques. Biochar particles were compared in soilless media and after deposition in soil. Scanning electron microscopy (SEM) observations and characterization of the biochar demonstrated structural heterogeneity within and among biochar particles. Fungal colonization in and on biochar particles was observed using light, fluorescence and electron microscopy. Fluorescent brightener RR 2200 was more effective than Calcofluor White as a hyphal stain. Biochar retrieved from soil and observed using fluorescence microscopy exhibited distinct hyphal networks on external biochar surfaces. The extent of hyphal colonization of biochar incubated in soil was much less than for biochar artificially inoculated with fungi in a soilless medium. The location of fungal hyphae was more clearly visible using SEM than with fluorescence microscopy. Observations of biochar particles colonized by hyphae from soil posed a range of difficulties including obstruction by the presence of soil particles on biochar surfaces and inside pores. Extensive hyphal colonization of the surface of the biochar in the soilless medium contrasted with limited hyphal colonization of pores within the biochar. Both visualization and quantification of hyphal colonization of surfaces and pores of biochar were restricted by two-dimensional imaging associated with uneven biochar surfaces and variable biochar pore structure. There was very little colonization of biochar from hyphae in the agricultural soil used in this study.